The Implementation of a Business Feasibility Study at Warung Kopi Mandala - Az Zahra, Fatimah; Siregar, Saniyah Dwi Putri; Lestari, Sri Dwi; Vientiany, Dini (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to evaluate the business feasibility study of Warkop Agam Mandala as a micro-enterprise in the culinary sector using a business feasibility study approach. The analysis covers market and marketing, legal, technical and operational, management, financial, sharia and halal aspects, as well as economic, social, and environmental aspects. The method applied in this study is descriptive, with data collection through observation, interviews with the owner, and a short survey of 50 respondents, mostly students. The findings of this study indicate that Warkop Agam Mandala has good market opportunities and clear consumer segmentation, affordable prices, menu choices that suit customer preferences, a strategic business location, adequate layout, and opening hours that align with customer visiting times. In terms of management and finance, this business is managed in a simple but efficient manner, and is able to generate net profits every month with a payback period of around 7 to 9 months. Overall, Warkop Agam Mandala was deemed feasible and has the potential for growth, with the caveat that improvements in legality and management are needed to ensure business sustainability.